Exploring University Students’ Experiences of Differentiated Vocabulary Instruction in an EFL Classroom - Wiraningsih, Putu; Manik, Ni Putu Ines Marylena Candra; Budiarte, Agus (Jurnal Pendidikan Bahasa Inggris Proficiency, 2026)
This study investigated the implementation of Differentiated Instruction (DI) in an English as a Foreign Language (EFL) classroom, specifically within an Instructional Vocabulary course involving students of the English Language Education Department at a university. The study aimed to explore (1) how DI was implemented in the teaching of vocabulary, (2) the benefits perceived by students, and (3) the challenges encountered during its implementation. A qualitative research approach was employed, involving classroom observations and semi-structured interviews with 30 undergraduate students. The findings revealed that DI was implemented through the differentiation of content, process, and product, following Tomlinson’s framework. In the context of vocabulary learning, content differentiation was reflected in the use of varied lexical materials with different levels of difficulty, process differentiation was evident in interactive and collaborative vocabulary learning activities, and product differentiation allowed students to demonstrate vocabulary mastery through diverse outputs. The results indicated that DI contributed positively to students’ vocabulary development, particularly in enhancing engagement, motivation, and the acquisition and use of vocabulary in context. However, several challenges were identified, including issues related to time management, classroom organization, and the need for careful lesson preparation. The study suggests that DI can be effectively implemented in university-level vocabulary courses when lecturers design flexible learning activities that accommodate students’ diverse readiness levels, interests, and learning profiles.